Metal and resin joint integrated composite material
By using plasma electrolytic oxidation treatment on the metal surface to form an oxide film and optimize the composition of the electrolyte, the problem of taking into account the bonding strength and fatigue strength of the integrated metal-resin bonding composite material is solved, and a balance between high bonding strength and good fatigue strength is achieved.
Patent Information
- Application Number
- CN202510273247.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-10
AI Technical Summary
The existing integrated bonding composite materials of metal and resin can easily reduce the fatigue strength of the metal while increasing the bonding strength.
Plasma electrolytic oxidation treatment is used to form an oxide film on the metal surface to ensure that the water contact angle of the oxide film is ≤30° and the surface roughness Ra≤1μm. The combination of the electrolyte is optimized to improve the bonding strength between the metal and the resin.
The bonding strength between metal and resin is significantly improved, while the metal fatigue strength reduction caused by conventional treatment methods is avoided, and the problem of taking into account both bonding strength and fatigue strength is solved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a composite material for integrating metal and resin. Background Art
[0002] Composite materials are materials with new properties that are formed by physical or chemical methods from two or more materials with different properties. The application of composite materials is of great significance in the fields of aerospace, automotive industry and robot manufacturing. On the one hand, composite materials have the advantages of high strength, high stiffness and low density, which can effectively reduce their own weight, achieve lightweight, and improve movement efficiency and flexibility; on the other hand, composite materials have good electrical and thermal conductivity, high temperature resistance, corrosion resistance and wear resistance, and can adapt to various harsh working environments.
[0003] High-strength metals such as titanium, aluminum, and magnesium are widely used due to their unique performance advantages. For example, aluminum alloys have the characteristics of low density, high strength, specific strength close to high alloy steel, and specific stiffness exceeding steel; titanium alloys have the advantages of high strength and corrosion resistance. Carbon fiber reinforced resin composites, referred to as CFRP, have the advantages of high specific strength and good chemical stability, but due to the lack of interlaminar fiber reinforcement in the layered CFRP structure, its impact resistance is poor. In actual use, it is often necessary to combine with metal to form a composite material. For example, the metal-resin joint integrated composite material formed by titanium alloy and CFRP has obvious advantages in aerospace applications such as rocket fuel tanks, wing leading edges, and engine pods.
[0004] The biggest structural feature of the integrated composite material of metal and resin is the multi-layer interface. The performance of the bonding interface directly affects the final performance of the composite material. If the bonding interface is prone to interface stratification or even cracking during use, it will lead to a decrease in stiffness and strength. Taking the metal-resin integrated composite material formed by titanium alloy and CFRP as an example, due to the strong chemical activity of titanium, it is very easy to react with elements such as oxygen and nitrogen at room temperature to form a dense and inert passivation film on its surface. This passivation film greatly affects the bonding strength between the titanium alloy and the resin. At present, the metal surface needs to be treated before the preparation of the integrated composite material of metal and resin, and the ideal bonding state is achieved by improving the metal surface morphology.
[0005] Mechanical methods such as sandblasting and grinding wheel polishing can increase the roughness of the metal surface and increase the contact area with the resin, which is conducive to forming a mechanical connection during bonding and improving the bonding strength. However, when the mechanical method is used, as the roughness of the metal surface increases, the surface concave and convex defects will become the starting point of metal fatigue cracking, which will greatly reduce the fatigue strength of the metal. Although chemical treatment methods such as mixed acid method, oxalic acid method and phosphate chloride method can also increase the roughness of the metal surface and improve the bonding strength through chemical etching, as the metal dissolves and the surface roughness increases, the fatigue strength of the metal will be reduced, and there are also environmental problems such as toxic chemical treatment and wastewater treatment. In addition, although methods such as alkaline anodizing and chromic acid anodizing can improve the bonding strength without significantly increasing the surface roughness, the shortcomings of poor stability and moisture and heat resistance restrict practical use.
[0006] Therefore, for the integrated composite materials of metal and resin, how to improve the bonding strength without affecting the metal fatigue strength is an urgent problem to be solved. Summary of the invention
[0007] The present invention provides a metal-resin joint integrated composite material, which solves the problem in the related art that the bonding strength of the metal-resin joint integrated composite material and the fatigue strength of the metal cannot be taken into account at the same time.
[0008] The technical solution of the present invention is as follows: The present invention provides a composite material for integrating metal and resin. The metal surface for bonding with the resin is provided with an oxide film, which is obtained by plasma electrolytic oxidation of the metal. The water contact angle of the oxide film is ≤30°.
[0009] As a further technical solution, the surface roughness of the oxide film is Ra≤1 μm.
[0010] As a further technical solution, the thickness of the oxide film is 0.3~5μm.
[0011] As a further technical solution, the shear bonding strength between the metal and the resin is ≥36 MPa.
[0012] As a further technical solution, during the plasma electrolytic oxidation, the voltage is 30~450V and the temperature is 10~60°C.
[0013] As a further technical solution, during the plasma electrolytic oxidation, the electrolyte includes the following components: alkali metal hydroxide, layered compound and aminosilane coupling agent.
[0014] As a further technical solution, the concentration of the alkali metal hydroxide is 10-50 g / L, the concentration of the layered compound is 8-10 g / L, and the concentration of the aminosilane coupling agent is 5-8 g / L.
[0015] As a further technical solution, the resin is a carbon fiber reinforced resin composite material, and the carbon fiber reinforced resin composite material is a carbon fiber reinforced thermosetting resin composite material or a carbon fiber reinforced thermoplastic resin composite material.
[0016] As a further technical solution, in the carbon fiber reinforced thermosetting resin composite material, the thermosetting resin includes one of phenolic resin, epoxy resin, unsaturated polyester, and thermosetting polyimide; In the carbon fiber reinforced thermoplastic resin composite material, the thermoplastic resin includes one of polyamide, polyphenylene sulfide, thermoplastic polyimide and polyetheretherketone.
[0017] As a further technical solution, the surface of the carbon fiber reinforced resin composite material is treated by atmospheric plasma processing.
[0018] The working principle and beneficial effects of the present invention are: In the present invention, the metal surface bonded with the resin is provided with an oxide film obtained by plasma electrolytic oxidation. By ensuring that the water contact angle of the oxide film is ≤30°, it is beneficial for the resin to be better wetted and attached, so that the metal and the resin can be closely combined to form a strong interface connection, which can significantly improve the bonding strength between the metal and the resin. In addition, unlike conventional mechanical treatment methods and chemical treatment methods, the use of plasma electrolytic oxidation treatment can improve the bonding strength between the metal and the resin while avoiding the phenomenon of metal fatigue strength reduction caused by the roughening of the metal surface due to conventional treatment methods to form a fatigue cracking starting point. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] It should be understood that, unless the context clearly indicates otherwise, the terms "include", "comprises" or "having" used in this application refer to the presence of a certain element, but do not exclude the presence or addition of one or more other elements. In addition, "includes" and / or "comprising" used in this article indicate the presence of shapes, numbers, steps, operations, members, elements and / or their combinations, and do not exclude the presence or addition of one or more other shapes, numbers, operations, elements and / or their combinations.
[0021] The numerical range represented by "~" in this application refers to the numerical range including the numerical range specified as the lower limit and the upper limit respectively before or after the word. When multiple values of the upper limit or lower limit of any numerical range are mentioned, the range disclosed herein can be understood as a range with any one of the multiple upper limits mentioned as its upper limit and any one of the multiple lower limits as its lower limit.
[0022] The metal and resin integrated composite material according to an embodiment of the present invention will be described in detail below.
[0023] According to one aspect of the present invention, there is provided an integrated composite material of metal and resin, wherein the metal surface bonded to the resin is provided with an oxide film, wherein the oxide film is obtained by subjecting the metal to plasma electrolytic oxidation treatment, wherein the water contact angle of the oxide film is ≤30°, for example, it may be 0.7°, 2°, 4°, 6.5°, 7.8°, 11.2°, 16.6°, 19.8°, 25°, or 30°.
[0024] In the present invention, plasma electrolytic oxidation has the characteristics of high energy density. Through the joint action of plasma chemistry, electrochemistry and thermochemistry, the metal surface can be given hydrophilic properties, which helps to improve the interface bonding between metal and resin without generating fatigue cracking points, thus solving the problem that the bonding strength of the integrated composite material of metal and resin and the fatigue strength of the metal cannot be taken into account at the same time.
[0025] In the present invention, the water contact angle of the metal surface can be measured by using a commercially available contact angle meter. For example, the water contact angle of the metal surface can be a value measured by using a contact angle meter (model: JC200A).
[0026] In one embodiment of the present invention, the surface roughness Ra of the oxide film is ≤1 μm, for example, it can be 0.2 μm, 0.4 μm, 0.57 μm, 0.68 μm, 0.73 μm, 0.81 μm, or 1 μm.
[0027] In the present invention, when the surface roughness Ra of the metal surface is ≤1 μm, on the one hand, the effective contact area between the metal and the resin can be increased, the mechanical bite ability of the metal and resin joint can be enhanced, and the bonding strength of the metal and the resin can be improved; on the other hand, the fatigue cracking points caused by the large surface roughness can be reduced, preventing the decrease of the metal fatigue strength.
[0028] In the present invention, the surface roughness Ra of the metal surface can be measured by a commercially available surface roughness tester using a contact measurement method. For example, the surface roughness Ra of the metal surface can be a value measured by moving the metal surface in any direction using a TS2200 surface roughness tester using a contact measurement method.
[0029] In one embodiment of the present invention, the thickness of the oxide film is 0.3-5 μm, for example, 0.3 μm, 0.7 μm, 1.2 μm, 1.7 μm, 2.6 μm, 3.4 μm, 4.5 μm, or 5 μm.
[0030] In the present invention, the thickness of the oxide film may be a thickness measured by scanning electron microscope (SEM) observation of a cross section of the film, or may be a thickness measured using a known thickness gauge.
[0031] In one embodiment of the present invention, the oxide film has submicron-scale irregularities.
[0032] In the present invention, during the plasma electrolytic oxidation process, the plasma discharge can instantly reach a high temperature state of more than thousands of degrees, forming an oxide film with submicron-level concave and convex on the metal surface. The unique microstructure provides a good bonding point for the resin, and these submicron-level concave and convex are different from the surface roughening of sandblasting or pickling, and will not become the starting point of metal fatigue cracking. While improving the bonding strength between metal and resin, it does not affect the fatigue strength of the metal.
[0033] In one embodiment of the present invention, the maximum diameter length of the submicron-scale concavities and convexities is 0.1-1 μm, for example, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, or 1 μm.
[0034] In the present invention, the maximum diameter length of the concavities and convexities can be measured by observation using a scanning electron microscope (SEM).
[0035] In one embodiment of the present invention, the shear bonding strength between the metal and the resin is ≥36 MPa, for example, 36 MPa, 36.7 MPa, 37.2 MPa, 39.8 MPa, 40.1 MPa, 40.5 MPa, 41.2 MPa, 41.8 MPa.
[0036] In the present invention, the shear bonding strength between the metal and the resin can be tested by a universal testing machine, for example, the value can be measured by using a commercially available universal testing machine with reference to ASTM D3165-07 (2014).
[0037] In one embodiment of the present invention, during plasma electrolytic oxidation, the voltage is 30~450V and the temperature is 10~60°C. For example, the voltage can be 30V, 100V, 200V, 300V, 400V, 450V; the temperature can be 10°C, 20°C, 30°C, 40°C, 50°C, 60°C.
[0038] In the present invention, when the voltage is 30-450V, the stability of plasma electrolytic oxidation can be improved; when the temperature is 10-60°C, a good film forming speed can be ensured and burns caused by excessively intense plasma electrolytic oxidation can be prevented.
[0039] In one embodiment of the present invention, the time of plasma electrolytic oxidation is 10 to 60 minutes, for example, it can be 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or 60 minutes, and can be adjusted according to actual needs.
[0040] In one embodiment of the present invention, during plasma electrolytic oxidation, the cathode material includes one of stainless steel, graphite, and titanium.
[0041] In one embodiment of the present invention, during plasma electrolytic oxidation, the electrolyte comprises the following components: an alkali metal hydroxide, a layered compound and an aminosilane coupling agent.
[0042] In the present invention, by optimizing the composition of the electrolyte, the metal surface can be provided with hydroxyl and aminosilane, thereby improving the hydrophilicity of the metal surface. Aminosilane can play a bridging role between the metal and resin interfaces or directly participate in the cross-linking reaction of the subsequent resin, which is conducive to further improving the bonding strength of the metal and the resin. In addition, the layered compound and the aminosilane coupling agent in the electrolyte can work together, and the aminosilane molecules enter the interlayer of the layered compound, induce and promote the interlayer peeling of the layered compound through a hydrolysis reaction to form a large number of nano-sheet structures with a large specific surface area, thereby improving the effective contact area of the metal and the resin, and further improving the bonding strength of the metal and the resin without affecting the fatigue strength of the metal.
[0043] In the present invention, the alkali metal hydroxide may be any alkali metal hydroxide, preferably one or both of sodium hydroxide and potassium hydroxide, for example, may be sodium hydroxide, potassium hydroxide, or a combination of sodium hydroxide and potassium hydroxide.
[0044] In the present invention, the layered compound is preferably a cationic layered compound, which performs charge compensation through interlayer mobile cations, and has the characteristics of high specific surface area, good ion exchange capacity, adjustable interlayer distance, and interlayer peeling. The cationic layered compound can be a layered phosphate, a layered silicate, and a layered titanate. The layered phosphate can be a layered zirconium phosphate or a layered titanium phosphate; the layered silicate can be mica, talc, and montmorillonite; the layered titanate can be a layered sodium titanate salt, a layered potassium titanate salt, or a layered lithium titanate salt, for example, a layered sodium dititanate, a layered sodium trititanate, a layered potassium tetratitanate, or a layered lithium titanate.
[0045] In the present invention, the aminosilane coupling agent has two active groups, amino and alkoxy groups, for example, it can be γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane can be selected from KH550, WD-50 and A-1100, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane can be selected from KH792, A-1120.
[0046] In one embodiment of the present invention, in the electrolyte, the concentration of the alkali metal hydroxide is 10-50 g / L, the concentration of the layered compound is 8-10 g / L, and the concentration of the aminosilane coupling agent is 5-8 g / L. For example, the concentration of the alkali metal hydroxide can be 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L; the concentration of the layered compound can be 8 g / L, 9 g / L, 10 g / L; the concentration of the aminosilane coupling agent can be 5 g / L, 6 g / L, 7 g / L, 8 g / L.
[0047] In one embodiment of the present invention, the solvent of the electrolyte is water.
[0048] In one embodiment of the present invention, the metal includes one of titanium, aluminum, magnesium, titanium alloy, aluminum alloy, and magnesium alloy. For example, it can be pure titanium, pure aluminum, pure magnesium, TC4 titanium alloy, TA1 titanium alloy, TA2 titanium alloy, 1000 series aluminum alloy, 2000 series aluminum alloy, 3000 series aluminum alloy, LZ91MA magnesium alloy, AZ91D magnesium alloy, and AZ61A magnesium alloy.
[0049] In one embodiment of the present invention, the resin is a carbon fiber reinforced resin composite material, and the carbon fiber reinforced resin composite material is a carbon fiber reinforced thermosetting resin composite material or a carbon fiber reinforced thermoplastic resin composite material.
[0050] In one embodiment of the present invention, when the carbon fiber reinforced resin composite material is a carbon fiber reinforced thermosetting resin composite material, the thermosetting resin in the carbon fiber reinforced thermosetting resin composite material includes one of phenolic resin, epoxy resin, unsaturated polyester, and thermosetting polyimide, preferably a carbon fiber reinforced thermosetting epoxy resin composite material.
[0051] In one embodiment of the present invention, when the carbon fiber reinforced resin composite material is a carbon fiber reinforced thermoplastic resin composite material, the thermoplastic resin in the carbon fiber reinforced thermoplastic resin composite material includes one of polyamide, polyphenylene sulfide, thermoplastic polyimide, and polyetheretherketone, preferably a carbon fiber reinforced thermoplastic polyetheretherketone resin composite material.
[0052] In one embodiment of the present invention, the surface of the carbon fiber reinforced resin composite material is treated by atmospheric plasma processing.
[0053] In the present invention, atmospheric plasma surface treatment technology is used to process carbon fiber reinforced resin composite materials, which can stimulate the generation of active ions, chemically react with atoms on the surface of the carbon fiber reinforced resin composite materials, improve their performance, improve the wettability, adhesion and hydrophilicity of the surface of the carbon fiber reinforced resin composite materials, and avoid surface and sub-surface damage caused by contact stress, further improving the bonding strength between metal and resin. In addition, the treatment method does not require vacuum equipment, has a low processing cost, and is suitable for industrial applications.
[0054] In one embodiment of the present invention, during the atmospheric plasma processing, the power is 1000 W, the processing distance is 15 mm, the processing time is 60 s, and the processing atmosphere is air.
[0055] In one embodiment of the present invention, when the carbon fiber reinforced resin composite material is a carbon fiber reinforced thermosetting resin composite material, a binder needs to be added when preparing a composite material for bonding metal and resin. For example, a method for preparing a composite material for bonding TC4 titanium alloy and a carbon fiber reinforced thermosetting epoxy resin composite material comprises the following steps: A1. Laying and forming unidirectional carbon fiber epoxy prepreg, curing, and atmospheric plasma processing to obtain a carbon fiber reinforced thermosetting epoxy resin composite material; Among them, the model of unidirectional carbon fiber epoxy prepreg is NY9200GA / HF10A, purchased from Jiangsu Hengshen Fiber Material Co., Ltd., and the carbon fiber reinforced thermosetting epoxy resin composite material has a total of 12 layers, the single layer thickness is 0.125mm, and the ply is [0 / 90]. During curing, it is heated to 140°C at a rate of 2°C / min, pressurized to 0.2MPa and kept warm for 30min, and then heated to 180°C at a rate of 2°C / min, pressurized to 0.5MPa and kept warm. After keeping warm for 2.5h, stop heating and cool naturally; When the atmospheric plasma processing is performed, an atmospheric pressure plasma instrument (model RFD-200) is selected, the power is 1000W, the processing distance is 15mm, the processing time is 60s, and the processing atmosphere is air; A2, subjecting TC4 titanium alloy having a thickness of 1.6 mm to a plasma electrolytic oxidation treatment to obtain a treated titanium alloy; In the plasma electrolytic oxidation treatment, the electrolyte includes the following components in concentration: 10 g / L sodium hydroxide, 8 g / L layered zirconium phosphate, 5 g / L γ-aminopropyltriethoxysilane (model KH550), the solvent is water, and a constant voltage pulse electrolysis method is adopted, with a voltage of 30 V, a temperature of 10° C., a time of 10 min, a pulse width of 20 ms, and a pulse interval of 5 ms; A3, laying the layers in the order of carbon fiber reinforced thermosetting epoxy resin composite material, adhesive, and treated titanium alloy from top to bottom, and then clamping them in a flat mold and hot pressing and curing them on a flat hot press to obtain a bonded integrated composite material of TC4 titanium alloy and carbon fiber reinforced thermosetting epoxy resin composite material; Among them, the adhesive is a thermosetting epoxy resin film with a thickness of 0.33mm (model AF191K), and the hot pressing curing process is: curing pressure 0.3MPa, heating from room temperature, heating rate 2℃ / min, heating to 177℃ and keeping warm for 1h, then stopping heating, naturally cooling to below 60℃ and releasing pressure.
[0056] In one embodiment of the present invention, when the carbon fiber reinforced resin composite material is a carbon fiber reinforced thermoplastic resin composite material, a heating and melting method is used to prepare a composite material of metal and resin. For example, a method for preparing a composite material of TC4 titanium alloy and carbon fiber reinforced thermoplastic polyetheretherketone resin composite material comprises the following steps: B1, laminating and curing the prepreg, and performing atmospheric plasma processing to obtain a carbon fiber reinforced thermoplastic polyetheretherketone resin composite material; Among them, the prepreg model is APC-2, the specification is AS4, produced by ICI Composites Fiberite of the United Kingdom. When the layers are cured, there are a total of 12 layers, the thickness of a single layer is 0.125mm, and the ply is [0 / 90]; When the atmospheric plasma processing is performed, an atmospheric pressure plasma instrument (model RFD-200) is selected, the power is 1000W, the processing distance is 15mm, the processing time is 60s, and the processing atmosphere is air; B2, subjecting the TC4 titanium alloy having a thickness of 1.6 mm to a plasma electrolytic oxidation treatment to obtain a treated titanium alloy; In the plasma electrolytic oxidation treatment, the electrolyte includes the following components in concentration: 10 g / L sodium hydroxide, 8 g / L layered zirconium phosphate, 5 g / L γ-aminopropyltriethoxysilane (model KH550), the solvent is water, and a constant voltage pulse electrolysis method is adopted, with a voltage of 30 V, a temperature of 10° C., a time of 10 min, a pulse width of 20 ms, and a pulse interval of 5 ms; B3, laying the layers in the order of carbon fiber reinforced thermoplastic polyetheretherketone resin composite material, polyetheretherketone film, and treated titanium alloy from top to bottom, and then clamping them in a flat mold and hot pressing and curing them on a flat hot press to obtain a bonded integrated composite material of TC4 titanium alloy and carbon fiber reinforced thermoplastic polyetheretherketone resin composite material; Among them, the thickness of the polyetheretherketone film is 50μm, the model is Aptiv 1000 series films, produced by Victrex, and the hot pressing curing process is: heating from room temperature to 390°C, keeping warm for 20 minutes, and then cooling naturally. During the cooling process, a pressure of 0.6MPa is applied to the mold.
[0057] The present invention will be described in detail below with reference to examples. The embodiments according to the present invention described below can be modified into various forms, so the scope of the present invention should not be interpreted as being limited to the embodiments described in detail below. Embodiments are provided to help those skilled in the art to more easily understand the present invention.
[0058] Example 1 A method for preparing a composite material of metal and resin bonding integration comprises the following steps: A1. Laying and curing the unidirectional carbon fiber epoxy prepreg to obtain a carbon fiber reinforced thermosetting epoxy resin composite material; Among them, the model of unidirectional carbon fiber epoxy prepreg is NY9200GA / HF10A, purchased from Jiangsu Hengshen Fiber Material Co., Ltd., and the carbon fiber reinforced thermosetting epoxy resin composite material has a total of 12 layers, the single layer thickness is 0.125mm, and the ply is [0 / 90]. During curing, it is heated to 140°C at a rate of 2°C / min, pressurized to 0.2MPa and kept warm for 30min, and then heated to 180°C at a rate of 2°C / min, pressurized to 0.5MPa and kept warm. After keeping warm for 2.5h, stop heating and cool naturally; A2, subjecting TC4 titanium alloy having a thickness of 1.6 mm to a plasma electrolytic oxidation treatment to obtain a treated titanium alloy; In the plasma electrolytic oxidation treatment, the electrolyte includes the following components in concentration: 10 g / L sodium hydroxide, 8 g / L layered zirconium phosphate, 5 g / L γ-aminopropyltriethoxysilane (model KH550), the solvent is water, and a constant voltage pulse electrolysis method is adopted, with a voltage of 30 V, a temperature of 60° C., a time of 60 min, a pulse width of 20 ms, and a pulse interval of 5 ms; A3, laying the layers in the order of carbon fiber reinforced thermosetting epoxy resin composite material, adhesive, and treated titanium alloy from top to bottom, and then clamping them in a flat mold and hot pressing and curing them on a flat hot press to obtain a bonded integrated composite material of TC4 titanium alloy and carbon fiber reinforced thermosetting epoxy resin composite material; Among them, the adhesive is a thermosetting epoxy resin film with a thickness of 0.33mm (model AF191K), and the hot pressing curing process is: curing pressure 0.3MPa, heating from room temperature, heating rate 2℃ / min, heating to 177℃ and keeping warm for 1h, then stopping heating, naturally cooling to below 60℃ and releasing pressure.
[0059] Example 2 A method for preparing a composite material of metal and resin bonding integration comprises the following steps: B1, laminating and curing the prepreg to obtain a carbon fiber reinforced thermoplastic polyetheretherketone resin composite material; Among them, the prepreg model is APC-2, the specification is AS4, produced by ICI Composites Fiberite of the United Kingdom. When the layers are cured, there are a total of 12 layers, the thickness of a single layer is 0.125mm, and the ply is [0 / 90]; B2, subjecting the TC4 titanium alloy having a thickness of 1.6 mm to a plasma electrolytic oxidation treatment to obtain a treated titanium alloy; In the plasma electrolytic oxidation treatment, the electrolyte includes the following components in concentration: 50 g / L sodium hydroxide, 10 g / L layered potassium tetratitanate, 8 g / L γ-aminopropyltriethoxysilane (model KH550), the solvent is water, and a constant voltage pulse electrolysis method is adopted, with a voltage of 450 V, a temperature of 10° C., a time of 60 min, a pulse width of 20 ms, and a pulse interval of 5 ms; B3, laying the layers in the order of carbon fiber reinforced thermoplastic polyetheretherketone resin composite material, polyetheretherketone film, and treated titanium alloy from top to bottom, and then clamping them in a flat mold and hot pressing and curing them on a flat hot press to obtain a bonded integrated composite material of TC4 titanium alloy and carbon fiber reinforced thermoplastic polyetheretherketone resin composite material; Among them, the thickness of the polyetheretherketone film is 50μm, the model is Aptiv 1000 series films, produced by Victrex, and the hot pressing curing process is: heating from room temperature to 390°C, keeping warm for 20 minutes, and then cooling naturally. During the cooling process, a pressure of 0.6MPa is applied to the mold.
[0060] Example 3 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the γ-aminopropyltriethoxysilane in the electrolyte is replaced by an equal amount of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (model KH792).
[0061] Example 4 The only difference between this embodiment and embodiment 2 is that, in this embodiment, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane in the electrolyte is replaced by an equal amount of γ-mercaptopropyltrimethoxysilane (model KH580).
[0062] Example 5 The only difference between this embodiment and embodiment 2 is that, in this embodiment, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane in the electrolyte is replaced by an equal amount of γ-glycidyloxypropyltrimethoxysilane (model KH560).
[0063] Example 6 The only difference between this embodiment and embodiment 2 is that, in this embodiment, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane in the electrolyte is replaced with an equal amount of vinyltriethoxysilane 5 g / L (model A-151).
[0064] Example 7 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the layered potassium tetratitanate in the electrolyte is replaced by an equal amount of tunnel-shaped potassium hexatitanate.
[0065] Example 8 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the layered potassium tetratitanate in the electrolyte is replaced by an equal amount of tunnel-shaped potassium octitanate.
[0066] Example 9 The only difference between this embodiment and embodiment 2 is that in this embodiment, after the prepreg is laminated and cured, it is also subjected to atmospheric plasma processing. During the atmospheric plasma processing, an atmospheric normal pressure plasma instrument (model RFD-200) is selected with a power of 1000W, a processing distance of 15mm, a processing time of 60s, and a processing atmosphere of air.
[0067] Example 10 The difference between this embodiment and embodiment 1 is that, in this embodiment, the material is changed from TC4 titanium alloy to AA2024 aluminum alloy, and the AA2024 aluminum alloy is subjected to plasma electrolytic oxidation to obtain the treated aluminum alloy; Among them, during plasma electrolytic oxidation treatment, the electrolyte includes components with the following concentrations: 5g / L sodium hydroxide, 8g / L layered zirconium phosphate, 5g / L γ-aminopropyltriethoxysilane (model KH550), the solvent is water, and a constant voltage pulse electrolysis method is adopted with a voltage of 300V, a temperature of 60°C, a time of 30min, a pulse width of 20ms, and a pulse interval of 5ms.
[0068] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, the TC4 alloy is not subjected to plasma electrolytic oxidation, but is subjected to sulfuric acid anodization. During sulfuric acid anodization, the electrolyte is 25 g / L sulfuric acid (mass fraction is 98%), the solvent is water, and a DC constant voltage method is adopted with a voltage of 20 V, a temperature of 25° C., and a time of 15 min.
[0069] Comparative Example 2 The only difference between this comparative example and Example 1 is that in this comparative example, the TC4 alloy was not subjected to plasma electrolytic oxidation, but was subjected to sodium hydroxide anodization. During the sodium hydroxide anodization, the electrolyte was 30 g / L sodium hydroxide, the solvent was water, and a DC constant voltage method was adopted with a voltage of 16 V, a temperature of 90° C., and a time of 25 min.
[0070] Comparative Example 3 The difference between this comparative example and Example 1 is that in this comparative example, the TC4 alloy is not subjected to plasma electrolytic oxidation, but is pickled with a mixed aqueous solution of nitric acid and hydrofluoric acid; Among them, the mass fraction of nitric acid is 30%, the mass fraction of hydrofluoric acid is 3%, the volume ratio of nitric acid to hydrofluoric acid is 1:1, the pickling temperature is 40°C, and the pickling time is 10 minutes.
[0071] Comparative Example 4 The only difference between this comparative example and Example 10 is that in this comparative example, the aluminum alloy AA2024 was not subjected to plasma electrolytic oxidation, but was subjected to sulfuric acid anodization. During sulfuric acid anodization, the electrolyte was 25 g / L sulfuric acid (mass fraction 98%), the solvent was water, and a DC constant voltage method was adopted with a voltage of 18 V, a temperature of 20° C., and a time of 30 min.
[0072] The following performance tests were performed on the metal-resin joint integrated composite materials prepared in Examples 1 to 10 and Comparative Examples 1 to 4: ① Water contact angle of oxide film: measured using a contact angle meter (model JC200A); ②Surface roughness Ra of the oxide film: TS2200 surface roughness tester is used to measure by moving along the same direction on the metal surface using the contact measurement method; ③Thickness of oxide film: The thickness of oxide film was measured by cross-section observation using a scanning electron microscope (model JCM-5000); ④ Metal fatigue strength: refer to GB / T 3075-2021 "Axial force control method for fatigue test of metal materials" for measurement, using a high-frequency fatigue testing machine, a test frequency of 90-130Hz, a sine wave, a stress ratio R of -1, and a target number of cycles of 107 cycles.
[0073] ⑤ Shear bond strength between metal and resin: measured using a universal testing machine in accordance with ASTM D3165-07 (2014); The test results are shown in Table 1 below.
[0074] Table 1 Performance test results
[0075] By comparing Example 1 with Comparative Examples 1 to 3, it can be seen that the metal surface in the metal-resin integrated composite material has hydrophilicity after being treated with plasma electrolytic oxidation, which improves the bonding strength between the metal and the resin while avoiding the phenomenon of metal surface roughening caused by conventional treatment methods to form fatigue cracking starting points, resulting in reduced metal fatigue strength.
[0076] Comparison between Examples 2-3 and Examples 4-6 shows that when the components of the electrolyte include an aminosilane coupling agent, the bonding strength between the metal and the resin can be further improved without affecting the fatigue strength of the metal.
[0077] Comparison between Example 2 and Examples 7-8 shows that the layered compound in the electrolyte can produce a synergistic effect with the aminosilane coupling agent, and can further improve the bonding strength between the metal and the resin without affecting the fatigue strength of the metal.
[0078] Comparison between Example 2 and Example 9 shows that the atmospheric plasma surface treatment technology can be used to process carbon fiber reinforced resin composite materials, which can further improve the bonding strength between metal and resin without affecting the fatigue strength of the metal.
[0079] Example 10 shows that changing the metal from TC4 titanium alloy to AA2024 aluminum alloy can also improve the bonding strength between the metal and the resin without affecting the fatigue strength of the metal.
[0080] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite material for integrating metal and resin, characterized in that: An oxide film is provided on the metal surface bonded with the resin. The oxide film is obtained by subjecting the metal to plasma electrolytic oxidation treatment. The water contact angle of the oxide film is ≤30°.
2. The metal-resin joint integrated composite material according to claim 1, characterized in that: The surface roughness of the oxide film is Ra≤1 μm.
3. The metal-resin joint integrated composite material according to claim 1, characterized in that: The thickness of the oxide film is 0.3-5 μm.
4. The metal-resin joint integrated composite material according to claim 1, characterized in that: The shear bonding strength between the metal and the resin is ≥36 MPa.
5. The metal-resin joint integrated composite material according to claim 1, characterized in that: During the plasma electrolytic oxidation, the voltage is 30-450V and the temperature is 10-60°C.
6. The metal-resin joint integrated composite material according to claim 1, characterized in that: During the plasma electrolytic oxidation, the electrolyte The invention comprises the following components: an alkali metal hydroxide, a layered compound and an aminosilane coupling agent.
7. The metal-resin joint integrated composite material according to claim 6, characterized in that: The concentration of the alkali metal hydroxide is 10-50 g / L, the concentration of the layered compound is 8-10 g / L, and the concentration of the aminosilane coupling agent is 5-8 g / L.
8. The metal-resin joint integrated composite material according to any one of claims 1 to 7, characterized in that: The resin is a carbon fiber reinforced resin composite material, and the carbon fiber reinforced resin composite material is a carbon fiber reinforced thermosetting resin composite material or a carbon fiber reinforced thermoplastic resin composite material.
9. The metal-resin joint integrated composite material according to claim 8, characterized in that: In the carbon fiber reinforced thermosetting resin composite material, the thermosetting resin includes one of phenolic resin, epoxy resin, unsaturated polyester and thermosetting polyimide; In the carbon fiber reinforced thermoplastic resin composite material, the thermoplastic resin includes one of polyamide, polyphenylene sulfide, thermoplastic polyimide and polyetheretherketone.
10. The metal-resin joint integrated composite material according to claim 8, characterized in that: The surface of the carbon fiber reinforced resin composite material is processed by atmospheric plasma.
Citation Information
Patent Citations
Composite material with magnesium alloy as base body and manufacturing method thereof
CN102582146A
Synergistic surface treatment method for improving bonding performance of carbon fiber composite material
CN117621429A
Metal with surface treated by silane coupling agent, treatment method and high-frequency high-speed signal transmission base material
CN119421342A
Welded joint of carbon fiber-reinforced thermoplastic resin molding and metal
JP2016034734A
Metal / fiber-reinforced plastic composite structure
JP2018167418A